Are older drivers' driving patterns during an on-road driving task representative of their real-world driving patterns?. (28th December 2018) - Koppel, S.; Charlton, J. L.; Hua, P.; Liu, P. Y.; Pham, H.; Stephan, K.; Logan, D.; St. Louis, R. M.; Gao, G.; Griffiths, D.; Williams, G.; Witharanage, T.; et al.
Abstract: Objective: The current study investigated whether older drivers' driving patterns during a customized on-road driving task were representative of their real-world driving patterns. Methods: Two hundred and eight participants (male: 68.80%; mean age = 81.52 years, SD = 3.37 years, range = 76.00–96.00 years) completed a customized on-road driving task that commenced from their home and was conducted in their own vehicle. Participants' real-world driving patterns for the preceding 4-month period were also collected via an in-car recording device (ICRD) that was installed in each participant's vehicle. Results: During the 4-month period prior to completing the on-road driving task, participants' median real-world driving trip distance was 2.66 km (interquartile range [IQR] = 1.14–5.79 km) and their median on-road driving task trip distance was 4.41 km (IQR = 2.83–6.35 km). Most participants' on-road driving task trip distances were classified as representative of their real-world driving trip distances (95.2%, n = 198). Conclusions: These findings suggest that most older drivers were able to devise a driving route that was representative of their real-world driving trip distance. Future research will examine whether additional aspects of the on-road driving task (e.g., average speed, proportion of trips in different speed zones) are representative of participants' real-world driving patterns.